Condiciones editoriales de las bases de datos de Redalyc y Sciencedirect para publicaciones en revistas científicas en temas de contabilidad. - Ñamo Hipo, Sara Elena (My University, 2022)
Scientific publications have the task of updating, refuting and socializing knowledge in the different disciplines, being the official mechanism to make content and information transparent through indexed databases. The objective of the study is to determine the similarities and differences between the editorial conditions of the scientific bases of Redalyc and Sciencedirect through a comparative analysis. A descriptive methodology is applied, analyzing the characteristics among the guidelines for authors in six scientific journals related to the subject of accounting and auditing, of which three belong to the regional current and three to the mainstream. The results show that the similarities between the reviewed journals are format, structure and content; while their differences are costs, frequency of publication, references and evaluation criteria assessing originality, scientific quality, arguments, citations and interests of the authors. The regional current databases are free, give more specific guidelines and seek to encourage scientific production in academic institutions; mainstream ones are paid, prefer inclusive language and their goal is to delve into knowledge that improves the quality of life of society.
Las publicaciones científicas tienen como consigna actualizar, refutar y socializar conocimientos en las diferentes disciplinas, siendo el mecanismo oficial para transparentar contenidos e información a través de bases de datos indexadas. El objetivo del estudio es determinar las similitudes y diferencias entre las condiciones editoriales de las bases científicas de Redalyc y Sciencedirect mediante un análisis comparativo. Se aplica una metodología del tipo descriptivo, analizando las características entre las directrices para autores en seis revistas científicas relacionadas a la temática de contabilidad y auditoría, de las cuáles tres pertenecen a corriente regional y tres de corriente principal. En los resultados se aprecia que las semejanzas entre las revistas revisadas son formato, estructura y contenidos; mientras que sus diferencias son costos, frecuencia de publicación, referencias y criterios de evaluación valorando la originalidad, calidad científica, argumentos, citas e intereses de los autores. Las bases de datos de corriente regional son gratuitas, dan directrices más específicas y buscan incentivar la producción científica en instituciones académicas; las de corriente principal son pagadas, prefieren lenguaje inclusivo y su meta es profundizar en saberes que mejoren la calidad de vida de la sociedad.
Keywords: CONDICIONES EDITORIALES; REDALYC; SCIENCEDIRECT; DIFERENCIAS